Teaching the Methodology of Sociology Using Digital Resources (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The advent of the digital era has become a serious challenge for researchers in various fields of scientific knowledge. Sociology, which tried to give an adequate answer to the question of how the modern world is changing, did not stand aside. The focus of digital sociologists is the digital society, which arises thanks to the development and implementation of modern technological infrastructure, represented by key digital technologies: communication networks, big data technologies, algorithms and complex algorithmic systems, platforms, artificial intelligence technologies, cloud computing, augmented and virtual technologies reality, etc.This article examines the teaching of sociology methodology using digital resources. Digital sociology is also considered as a professional sociological practice, which includes teaching the discipline, carrying out scientific communications and disseminating the results of the scientific activities of sociologists.